Understanding The Vietnamese Child’s Authoring of The Self Through Multimodal Stories - Pham, Hoa; Pham, Thu (Universitas Negeri Semarang, 2023)
Guided by Bakhtin's theory of dialogism, we understand that children's identities emerge from an open-ended process in which they articulate external resources and integrate them into their ideas to author themselves. This qualitative study draws on Bakhtin's theory of dialogism and a semiotic lens of multimodality to discuss how Linh, a Vietnamese four-year-and-half girl, authored herself in her multimodal stories across home and preschool. Linh's stories were gathered through close observation and were analyzed in connection with her parents’ and teachers’ narratives. Two narrative chains of her stories were chosen to describe how the child articulated adults’ utterances and cultural resources via her multimodal language to express her emergent identities. Findings initiate early childhood education (ECE) teachers and researchers to see children’s stories and identities in ongoingness and attend to the fluidity within children’s ECE settings, homes, and cultures.